Análise de ambiguidade em métodos de campo potenciais através de análise fatorial, Q-Modal - LOPES, Simone da Graça Fraiha (Universidade Federal do Pará, 2014)
A method is presented to analyze ambiguity in geophysical interpretation. Initially, alternative solutions are obtained which are assumed to be representative of the region in parameter space where ambiguity is more pronounced. In a second stage, these solutions are grouped and ordered using Q-mode factor analysis. The method was applied to synthetic potential field data where some important causes of ambiguity are simulated, such as discretizing and truncation of the anomaly, and the presence of random and geologic noise. A single prism is employed as an interpretation model and in both gravity and magnetic cases the prism depth extent stands out as the main cause of ambiguity. The second cause is either the depth to the top when the anomaly presents a strong signal, or the width when the anomaly presents a weak signal. The presence of random noise is not an important factor leading to ambiguity. On the other hand, the presence of interfering sources is a strong fator in both gravity and magnetic interpretation. The application of the method to real anomalies illustrates its importance in defining alternative solutions, and the importance of the a priori information in the establishment of the causes of ambiguity. The presented method may be applied at any stage of an exploration project. At each stage it provides relevant information which may be useful in planning the next stage. Compared with other methods usually employed in ambiguity analysis such as confidence regions, for exemple, the proposed method has the advantage of requiring no statistical assumptions about the error distribuition.